Pengembangan Buku Ajar Manajemen Keuangan Penggabungan Arthasastra dengan Manajemen Keuangan Kontemporer - Susanti, Komang Dewi; Oktaviana, Duwi; Kusuma, Anak Agung Gede Mahendra (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This research aims to develop a financial management textbook that combines principles from the Arthashastra, a classic ancient Indian economic text, with contemporary financial management concepts. The research methodology involves literature analysis, case studies, and surveys to evaluate the effectiveness and relevance of the material developed. The research results show that the integration of principles from the Arthashastra with modern theories provides a more holistic and in-depth approach to financial management. This textbook enriches the curriculum with historical and cultural dimensions, enhances students' analytical and critical skills, and offers useful practical insights into risk management, fiscal policy and investment. The survey showed a positive response from lecturers and students, who considered this textbook as an effective tool in the learning process. This research concludes that combining these two approaches not only enriches academic understanding but also improves the quality of education and the relevance of financial management practices. In this way, it is hoped that this textbook can better prepare graduates to face challenges in the world of global finance and contribute to the development of this discipline as a whole.